Magnon-induced electric polarization and magnon Nernst effects - D. Quang To; Federico Garcia-Gaitan; Yafei Ren; Joshua M. O. Zide; M. Benjamin Jungfleisch; John Q. Xiao; Branislav K. Nikolić; Garnett W. Bryant; Matthew F. Doty (Proceedings of the National Academy of Sciences, 2025)
Magnons offer a promising path toward energy-efficient information transmission and the development of next-generation classical and quantum computing technologies. However, efficiently exciting, manipulating, and detecting magnons remains a critical need. We show that magnons, despite their charge-neutrality, can induce electric polarization through their spin and orbital moments. This effect is governed by system symmetry, magnon band hybridization, and interactions with other quasiparticles. We calculate the electric polarization induced by magnons in two-dimensional collinear honeycomb and noncollinear antiferromagnets (AFMs), showing that the presence of the Dzyaloshinskii–Moriya interaction yields a finite net electric polarization. In NiPSe 3 , a collinear honeycomb AFM with Zigzag order, the induced net electric polarization is about three orders of magnitude greater than in MnPS 3 , a collinear honeycomb AFM with Néel phase. In the noncollinear AFM KFe 3 (OH) 6 (SO 4 ) 2 , the net electric polarization can be tuned via magnon hybridization, which can be controlled by external magnetic fields. These findings reveal that electric fields could be used to both detect and manipulate magnons under certain conditions by leveraging their spin and orbital angular moment. They also suggest that the discovery or engineering of materials with substantial magnon orbital moments could enhance practical uses of magnons for future computing and information transmission applications.